2018
DOI: 10.1016/j.pmedr.2018.08.009
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive evaluation of male health in four communities in rural Honduras

Abstract: PODEMOS (Partnership for Ongoing Developmental, Educational and Medical Outreach Solutions) has been a long-standing healthcare provider in 4 communities in northern rural Honduras. In this study, we sought to understand and quantify the health challenges faced by men in the rural communities served by PODEMOS in order to improve the way PODEMOS delivers healthcare. Between June and July of 2015, we conducted 104 structured survey interviews with men 18 years and older in rural Honduras. We found that most men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…41 In this analysis, rural residence is associated with lower HD prevalence for both men and women. These findings align with studies conducted, one in Honduras among male residents of rural areas (percent drinking alcohol heavily in males = 0%) 42 and another in a Latin American country where higher consumption levels were observed in urban areas (0.34% more likely to have HD than individuals with rural residences). 43 It is worth noting that some reviews have reported higher alcohol consumption in rural areas.…”
Section: Heavy Drinking In Hondurassupporting
confidence: 89%
“…41 In this analysis, rural residence is associated with lower HD prevalence for both men and women. These findings align with studies conducted, one in Honduras among male residents of rural areas (percent drinking alcohol heavily in males = 0%) 42 and another in a Latin American country where higher consumption levels were observed in urban areas (0.34% more likely to have HD than individuals with rural residences). 43 It is worth noting that some reviews have reported higher alcohol consumption in rural areas.…”
Section: Heavy Drinking In Hondurassupporting
confidence: 89%